2007
DOI: 10.1093/schbul/sbm116
|View full text |Cite
|
Sign up to set email alerts
|

The Dream as a Model for Psychosis: An Experimental Approach Using Bizarreness as a Cognitive Marker

Abstract: Many previous observers have reported some qualitative similarities between the normal mental state of dreaming and the abnormal mental state of psychosis. Recent psychological, tomographic, electrophysiological, and neurochemical data appear to confirm the functional similarities between these 2 states. In this study, the hypothesis of the dreaming brain as a neurobiological model for psychosis was tested by focusing on cognitive bizarreness, a distinctive property of the dreaming mental state defined by disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 38 publications
6
49
1
1
Order By: Relevance
“…In addition to the above described common features of schizophrenia and dreaming, research on cognitive bizarreness conducted by Scarone and colleagues [29] supports the hypothesis that due to similarities between these two states, a dreaming brain may be a useful model for this disease. The level of cognitive bizarreness, defined as discontinuity and incongruity of dream perception and cognition is comparable in both non-clinical subjects, and ones suffering from schizophrenia.…”
Section: Common Phenomenological Features Of Schizophrenia and Dreamingmentioning
confidence: 77%
See 3 more Smart Citations
“…In addition to the above described common features of schizophrenia and dreaming, research on cognitive bizarreness conducted by Scarone and colleagues [29] supports the hypothesis that due to similarities between these two states, a dreaming brain may be a useful model for this disease. The level of cognitive bizarreness, defined as discontinuity and incongruity of dream perception and cognition is comparable in both non-clinical subjects, and ones suffering from schizophrenia.…”
Section: Common Phenomenological Features Of Schizophrenia and Dreamingmentioning
confidence: 77%
“…The level of cognitive bizarreness, defined as discontinuity and incongruity of dream perception and cognition is comparable in both non-clinical subjects, and ones suffering from schizophrenia. A comparison of stories from the Thematic Apperception Test obtained from both patients and non-clinical subjects revealed that although the level of cognitive bizarreness is significantly higher in the former than in the latter, it still oscillates at a level similar to that which occurs in dreams [29]. Therefore, it seems that while bizarreness constitutes a kind of cognitive model for dreaming mental state (for both clinical and non-clinical populations), it is still present as a characteristic feature of waking cognitive organization in schizophrenia.…”
Section: Common Phenomenological Features Of Schizophrenia and Dreamingmentioning
confidence: 96%
See 2 more Smart Citations
“…Beginning with Freud and Jung, researchers have drawn similarities between dreaming and psychosis. These similarities range from phenomenological to neurobiological, qualitatively manifested as a loosening of associations, incongruity and bizarreness of personal experience, and distortion of time and space parameters (Scarone et al, 2008). Reviewing the content of our 25-topic solution, we see no reason to interpret the clustering of words within any given topic as incongruous nor do we detect support for the content to be evaluated as "bizarre" (Hobson et al, 1987).…”
Section: The Topical Structure Of Dreamsmentioning
confidence: 67%